Comparison of a high and a low intensity smoking cessation intervention in a dentistry setting in Sweden - a randomized trial - Rosenblad Andreas; Johansson Pia; Tillgren Per; Tegelberg Åke; Nohlert Eva; Helgason Ásgeir R (BMC, 2009)
Abstract Background Tobacco is still the number one life style risk factor for ill health and premature death and also one of the major contributors to oral problems and diseases. Dentistry may be a potential setting for several aspects of clinical public health interventions and there is a growing interest in several countries to develop tobacco cessation support in dentistry setting. The aim of the present study was to assess the relative effectiveness of a high intensity intervention compared with a low intensity intervention for smoking cessation support in a dental clinic setting. Methods 300 smokers attending dental or general health care were randomly assigned to two arms and referred to the local dental clinic for smoking cessation support. One arm received support with low intensity treatment (LIT), whereas the other group was assigned to high intensity treatment (HIT) support. The main outcome measures included self-reported point prevalence and continuous abstinence (≥ 183 days) at the 12-month follow-up. Results Follow-up questionnaires were returned from 86% of the participants. People in the HIT-arm were twice as likely to report continuous abstinence compared with the LIT-arm (18% vs. 9%, p = 0.02). There was a difference (not significant) between the arms in point prevalence abstinence in favour of the HIT-protocol (23% vs. 16%). However, point prevalence cessation rates in the LIT-arm reporting additional support were relatively high (23%) compared with available data assessing abstinence in smokers trying to quit without professional support. Conclusion Screening for willingness to quit smoking within the health care system and offering smoking cessation support within dentistry may be an effective model for smoking cessation support in Sweden. The LIT approach is less expensive and time consuming and may be appropriate as a first treatment option, but should be integrated with other forms of available support in the community. The more extensive and expensive HIT-protocol should be offered to those who are unable to quit with the LIT approach in combination with other support. Trial Registration Trial registration number: NCT00670514